Antagonistic potentiality of soil-borne fungi against the major seed-borne pathogenic fungi of rice in Bangladesh (Dhaka University Journal of Biological Sciences, 2025)
A total of twenty BRRI rice varieties i.e., BRRI dhan 56 to BRRI dhan 75 were collected from Bangladesh Rice Research Institute (BRRI) to detect the seed borne fungi associated with seeds of selected rice varieties. Four antagonistic potentials of soil fungi comprising three species of Aspergillus viz., A. flavus Link, A. fumigatus Fresenius, A. niger van Tieghem and species of Trichoderma viride Pers. were used against six important rice pathogenic fungi (i.e. Bipolaris oryzae (Breda de Haan) Shoemaker, Curvularia lunata (Wakker) Boedijn, Fusarium equiseti (Corda) Saccardo. Fusarium fujikuroi Nirenberg, Microdochium fisheri Hern.-Restr. and Crous. and Nigrospora oryzae (Berk. & Br.) for the purpose of biological control. In dual culture colony interaction out of four antagonistic fungi, T. viride showed the highest growth inhibition (87.15%) against Fusarium fujikuroi. The maximum inhibition (82.63%) of radial growth of the test pathogens were observed in case of T. viride owing to the volatile metabolites. On the other hand, the highest amount for the effect of non-volatile metabolites of T. viride on N. oryzae and F. fujikuroi at 20% concentration. The present investigation suggests that the isolates of Trichoderma is a biocontrol agent that can help control seed borne fungi in rice.Dhaka Univ. J. Biol. Sci. 34(1): 109-117, 2025 (January)